2022
DOI: 10.1186/s12888-022-04184-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of treatment resistant depression among major depressive disorder patients in Israel

Abstract: Introduction Major depressive disorder (MDD) is one of the most common mental disorders worldwide, estimated to affect 10–15% of the population per year. Treatment resistant depression (TRD) is estimated to affect a third of these patients who show difficulties in social and occupational function, decline of physical health, suicidal thoughts and increased health care utilization. We describe the prevalence of MDD, TRD and associated healthcare resource utilization in Maccabi Healthcare Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
2
5
0
1
Order By: Relevance
“…47 Although PD is among the most common comorbid psychiatric conditions in TRD, none of these studies reported on participants with both TRD and PD. [48][49][50] Our study supports previous studies showing that a pharmacotherapy including quetiapine can improve subjective sleep in TRD independently of the presence of PD or not. However, we found a greater improvement of sleep quality in TRD/PD+ compared with TRD/PD− treated with a pharmacotherapy, which included quetiapine.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…47 Although PD is among the most common comorbid psychiatric conditions in TRD, none of these studies reported on participants with both TRD and PD. [48][49][50] Our study supports previous studies showing that a pharmacotherapy including quetiapine can improve subjective sleep in TRD independently of the presence of PD or not. However, we found a greater improvement of sleep quality in TRD/PD+ compared with TRD/PD− treated with a pharmacotherapy, which included quetiapine.…”
Section: Discussionsupporting
confidence: 89%
“…In a 20-week open trial with quetiapine (315 ± 109 mg, flexible dose), 14 patients with TRD showed a decrease of more than 4 points on the TSS at their first time of measurement (eg, after only 2 weeks of treatment) 47 . Although PD is among the most common comorbid psychiatric conditions in TRD, none of these studies reported on participants with both TRD and PD 48–50 . Our study supports previous studies showing that a pharmacotherapy including quetiapine can improve subjective sleep in TRD independently of the presence of PD or not.…”
Section: Discussionsupporting
confidence: 85%
“…A similar French research detected 25.8 people suffering from TRD per 10,000 patients ( 41 ). Furthermore, TRD proportion was estimated to be 4.2% in Italy ( 42 ), 24.4% in Israel ( 43 ) and 19.6% in Thailand ( 44 ). Although prevalence data are heterogeneous, the common element is that TRD is quite frequent in ordinary clinical practice.…”
Section: Results From the Narrative Clinical Reviewmentioning
confidence: 99%
“…Differences in the definition of TRD have resulted in highly variable estimates of its prevalence rate 99 . TRD is often stated to affect approximately 30% of persons receiving antidepressant treatment in research settings, while its prevalence in real world practice is estimated to range between 6 and 55% 32,98‐101 .…”
Section: Prevalence Of Treatment‐resistant Depressionmentioning
confidence: 99%